A cross-sectional survey of critical care services in Sri Lanka: A lower middle-income country - Haniffa, R; De Silva, A; Iddagoda, S; Batawalage, H; De Silva, S; Mahipala, P; Dondorp, A; de Keizer, N; Jayasinghe, S (W.B. Saunders, 2014)
Purpose: To describe the extent and variation of critical care services in Sri Lanka as a first step towards the development of a nationwide critical care unit (CCU) registry. Materials and Methods: A cross-sectional survey was conducted in all state CCUs by telephone or by visits to determine administration, infrastructure, equipment, staffing, and overall patient outcomes. Results: There were 99 CCUs with 2.5 CCU beds per 100. 000 population and 13 CCU beds per 1 000 hospital beds. The median number of beds per CCU was 5. The overall admissions were 194 per 100. 000 population per year. The overall bed turnover was 76.5 per unit per year, with CCU mortality being 17%.Most CCUs were headed by an anesthetist. There were a total of 790 doctors (1.6 per bed), 1 989 nurses (3.9 per bed), and 626 health care assistants (1.2 per bed). Majority (87.9%) had 1:1 nurse-to-patient ratio, although few (11.4%) nurses had received formal intensive care unit training. All CCUs had basic infrastructure (electricity, running water, piped oxygen) and basic equipment (such as electronic monitoring and infusion pumps). Conclusion: Sri Lanka, a lower middle-income country has an extensive network of critical care facilities but with inequalities in its distribution and facilities. © 2014 Elsevier Inc.